2016
DOI: 10.1177/0738894215570430
|View full text |Cite
|
Sign up to set email alerts
|

Centers of gravity and war outcomes

Abstract: Bargaining models argue that wars usually terminate when the information gap closes enough to create a bargaining range. Although this convergence is assumed to be straightforward, factors that identify the information regarding the likely military outcome to the belligerents have not been identified. One of Clausewitz's main ideas was that states can win wars by attacking the enemy's centers of gravity, which I argue provide an important way through which information convergence is achieved. I examine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For that purpose, the Tallinn Center organizes tuition and assists member countries in improving cyber defense programs, and the allies expand their early prevention resources in the form of a common network of monitoring nodes and sensors. NATO uses the defense planning process to promote the development of cyber defense capabilities of allies, helping individual member countries and optimizing information exchange, cooperation and compatibility (Quackenbush, 2015).…”
Section: Nato Information Security Managementmentioning
confidence: 99%
“…For that purpose, the Tallinn Center organizes tuition and assists member countries in improving cyber defense programs, and the allies expand their early prevention resources in the form of a common network of monitoring nodes and sensors. NATO uses the defense planning process to promote the development of cyber defense capabilities of allies, helping individual member countries and optimizing information exchange, cooperation and compatibility (Quackenbush, 2015).…”
Section: Nato Information Security Managementmentioning
confidence: 99%
“…From the Russian perspective "war is now conducted by roughly 4:1 ratio of nonmilitary and military" means (Bartles, 2016). The primary target of 4GW is an identity core and ideas are a center of gravity (Quackenbush, 2015) by using nonmilitary means (Davis, 2014). "Fourth Generation war is also marked by a return to a world of cultures, not merely states, in conflict" (Lind, 2004).…”
Section: Fig 1 Corners Of State Securitymentioning
confidence: 99%
“…Using a sample of all wars from 1816 to 2000, the authors find that democracies tend to fight alongside larger coalitions and that states that fight alongside larger coalitions are more likely to win wars. One recent study even used k -adic data to examine war outcomes and found that democracy was a significant predictor of war outcomes (Quackenbush, 2015). Although the focus of that study was on centers of gravity rather than democracy, the results suggest that previous studies supporting the idea of a democratic advantage may not have been seriously affected by the misuse of dyadic data.…”
Section: Dyadic Datasets and Multilateral Eventsmentioning
confidence: 99%